2004
DOI: 10.2527/2004.8282451x
|View full text |Cite
|
Sign up to set email alerts
|

Different measures of energetic efficiency and their phenotypic relationships with growth, feed intake, and ultrasound and carcass merit in hybrid cattle1

Abstract: Residual feed intake (RFI) has been proposed as an index for determining beef cattle energetic efficiency. Although the relationship of RFI with feed conversion ratio (FCR) is well established, little is known about how RFI compares to other measures of efficiency. This study examined the phenotypic relationships among different measures of energetic efficiency with growth, feed intake, and ultrasound and carcass merit of hybrid cattle (n = 150). Dry matter intake, ME intake (MEI), ADG, metabolic weight (MWT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
73
1
16

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(114 citation statements)
references
References 19 publications
22
73
1
16
Order By: Relevance
“…These findings agree with those of Gomes et al (2012) for carcass backfat in steers. However, Nkrumah et al (2004) and Basarab et al (2007) found that RFI had a significant positive correlation (r = 0.25, 0.22; respectively) with carcass fat grade. The contrasting results for carcass fatness traits may arise from different measures of classifying carcass fatness.…”
Section: Discussionmentioning
confidence: 91%
“…These findings agree with those of Gomes et al (2012) for carcass backfat in steers. However, Nkrumah et al (2004) and Basarab et al (2007) found that RFI had a significant positive correlation (r = 0.25, 0.22; respectively) with carcass fat grade. The contrasting results for carcass fatness traits may arise from different measures of classifying carcass fatness.…”
Section: Discussionmentioning
confidence: 91%
“…Em relação ao PVI, PVF e PM, os resultados aqui obtidos estão em concordância com os relatos de que o CAR não está ligado às medidas de tamanho corporal, como previamente descrito por Arthur et al (2001b) e Carstens et al (2002. Para TCR e TK, semelhante ao encontrado por Nkrumah et al (2004) consideração os pesos vivos e o ganho de peso dos animais, e estes se mostraram similares neste experimento, justifica-se a ausência de significância para essas medidas.…”
Section: Methodsunclassified
“…Nkrumah et al (2004) descreveram correlações muito parecidas entre CA e GMD, TCR e TK para bovinos mestiços, com coeficientes de, respectivamente, -0,63, -0,75 e -0,73. Para animais Nelore, Santana (2009) estimou correlações de -0,85 para CA e GMD, e de 0,50 entre CA e PVI, este último muito próximo ao exposto para cordeiros neste estudo.…”
Section: Methodsunclassified
“…24 Researchers evaluating residual feed intake (RFI) found distinct differences in feeding behaviors among high and low RFI calves using both the GrowSafe and Insentec monitoring systems. 60,61 Since feed inputs represent one of the largest costs in producing beef, monitoring behaviors that may identify calves with less than ideal feed efficiencies may be beneficial. 62 Monitoring the feeding behavior of an animal over a period of time allows establishment of a baseline against which deviations in subsequent behavioral patterns can be evaluated.…”
Section: Feed Intake and Behavioral Monitoringmentioning
confidence: 99%